Implementation of School-Based Management in Improving The Character Quality of Elementary School Students - Panggabean, Rika Rosanti; Astari, Yulisa Puji; Sari, Indah Permata; Rohmadani; Safrudin (Indonesian Values and Character Education Journal, 2022)
Principals face various problems, including the lack of disciplined educators and the lack of principal communication with educators and teaching staff. This study aimed to analyze the implementation of school-based management (SBM) in improving the character quality of elementary school students. This study uses a descriptive method with a qualitative approach. Data collection techniques used in this study were observation, interviews, and documentary studies. The data analysis technique used in this research is qualitative data analysis. The results showed the implementation of School-Based Management in forming student character. Program planning begins with various socializations at coordination meetings between schools, committees, and related parties. Student character formation can be formed by collaborating in each subject, namely applying discipline, good manners, and respect for others. One of the moral values ​​teachers must instill in elementary school education is cultivating character values ​​in students. The implementation of SBM is in line with the education decentralization policy that provides management autonomy according to its authority and provides good services to all internal and external interested parties in fulfilling the character of high-quality students for a nation.